Lecturers Perceived Proficiency in The Use of Virtual Classrooms for Instruction in Colleges of Education - Ekunola, Gbadebo Temitope; Obielodan, Omotayo Olabo; Babalola, Ebenezer Omolafe (ASEAN Journal of Educational Research and Technology, 2022)
Virtual Classrooms (VCs) are digital platforms that create an atmosphere by integrating internet technologies in which instructors, students. Scholars and interested persons can engage, connect, communicate and describe their thought and opinions in a well-organized, pedagogical, and professional manner. The study investigated lecturers’ perceived proficiency in the use of VCs for teaching and learning in colleges of education in Ondo State, south-western Nigeria. The objectives were to (i) investigate lecturers’ perceived proficiency in the use of Virtual Classrooms for instruction; (ii) determine the difference in lecturers’ gender on their perceived proficiency in the use of virtual classrooms for instruction; and (iii) investigate lecturers’ perceived proficiency in the use of virtual classrooms for instruction based on years of experience. Questionnaires were administered to 298 lecturers. Findings indicated that irrespective of gender, lecturers’ perceived proficiency towards the use of VCs do not vary, while lecturers’ perceived proficiency are influenced by their years of teaching experience with a statistical value of t (298) = 4.86, p = .000) in favor of less experienced lecturers’. The study recommended among others that concerned agencies and school management should sensitize, train, and provide an enabling environment that will encourage the use of VCs among COE lecturers irrespective of gender and years of teaching experience.